Induced and spontaneous colitis mouse models reveal complex interactions between IL-10 and IL-12/IL-23 pathways. (September 2019) - Hurtubise, Raphaël; Audiger, Cindy; Dominguez-Punaro, Maria C.; Chabot-Roy, Geneviève; Chognard, Gaëlle; Raymond-Marchand, Laurence; Coderre, Lise; Chemtob, Sylvain; Michnick, Stephen W.; Rioux, John D.; Lesage, Sylvie
Highlights: Absence of IL-12Rβ2 protects from both induced and spontaneous colitis in IL10 −/− mice. The contribution of IL-23R deficiency to colitis development is context dependent. Both IL-12 and IL-23 pathways are protective against spontaneous colitis. Inhibition of either IL-12 or IL-23 pathways yield distinct inflammatory signatures. Abstract: Crohn's disease (CD) and ulcerative colitis (UC) are the two major forms of inflammatory bowel disease (IBD). These idiopathic and chronic diseases result from inflammation of the gastrointestinal tract and are mainly mediated by the immune system. Genome wide association studies link genes of the IL-12 and IL-23 biology to both CD and UC susceptibility. IL-12 and IL-23 cytokines share a functional subunit, p40, and their respective receptors also share a functional subunit, IL-12Rβ1. However, clinical trials targeting p40, and thus inhibiting both IL-12 and IL-23 pathways, provided mitigated effects on IBD, suggesting context dependent effects for each cytokine. In addition to IL-12 and IL-23, genetic deficiencies in IL-10 also result in severe IBD pathology. We generated various mouse models to determine how IL-12 or IL-23 interacts with IL-10 in IBD pathology. Whereas defects in both IL-10 and IL-12R do not impact the severity of the Dextran Sulfate Sodium (DSS)-induced colitis, combined deficiencies in both IL-10 and IL-23R aggravate the disease. In contrast to DSS-induced colitis, defects in IL-12R and IL-23R both protect from the spontaneous colitis observed in IL10 −/− mice. Together, these studies exemplify the complexity of genetic and environmental interactions for identifying biological pathways predictive of pathological inflammatory processes.